An Analysis of Contractor Satisfaction on Owner Team Performance in Construction Projects (Case Study: Construction Projects in ITS) - Paus Usboko, Gregorius; Wahyu Adi, Tri Joko (KnE Social Sciences, 2020)
Subjective performance measurements have been developed on construction projects of various key stakeholders such as contractors, designers and consultants. These approaches are usually related to owner satisfaction, customer satisfaction, occupant satisfaction but very rarely consider contractor satisfaction. The performance of the contractor and owner are interdependent, and their interactions fundamentally determine the overall project performance. This research aims to analyze the level of contractor satisfaction with the team owner’s performance which in the end to improve the improvement (Continuous Improvement) where there are indicators of team’ owner performance that needs attention to be improved and improved and those that need to be maintained. Owner performance indicators include the owner’s understanding of project needs, finances, decision-making, management, adequate support for contractors, client attitudes, clarity of client/owner commitment goals, and the working relationship of the owner and contractor. These indicators were obtained from literature and interviews with practitioners. These indicators are then developed to improve the existing conceptual framework. The satisfaction is measured using the Customer Satisfaction Index (CSI) and priority variables that need to be improved are analyzed by the Importance Performance Analysis (IPA) method. The results of this study indicate the level of contractor satisfaction with the performance of the team owner from CSI calculations at the level of satisfaction. Meanwhile the results of the IPA show that financial indicators, one sub-indicator of support for contractors and one sub-indicator of the attitude of the owner must be improved. Keywords: Contractor satisfaction, Owner performance, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA).